2020
DOI: 10.1063/1.5134681
|View full text |Cite
|
Sign up to set email alerts
|

Defect properties of solar cells with layers of GaP based dilute nitrides grown by molecular beam epitaxy

Abstract: Real-time dynamic evolution monitoring of laser-induced exciton phase flips in 2D hybrid semiconductor (C 12 H 25 NH 3 ) 2 PbI 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…This type of defect appears under non-equilibrium growth conditions when a large number of gallium and phosphorus vacancies are formed and Si occupies the gallium vacancies. It is a frequently observed defect in GaP layers doped by silicon [20][21][22]. Silicon doping is expected here in the GaP layers because of Si residuals that can be incorporated during the GaP/Si structure growth.…”
Section: Resultsmentioning
confidence: 99%
“…This type of defect appears under non-equilibrium growth conditions when a large number of gallium and phosphorus vacancies are formed and Si occupies the gallium vacancies. It is a frequently observed defect in GaP layers doped by silicon [20][21][22]. Silicon doping is expected here in the GaP layers because of Si residuals that can be incorporated during the GaP/Si structure growth.…”
Section: Resultsmentioning
confidence: 99%
“…Одним из таких приоритетных направлений для солнечной энергетики является создание двухпереходного солнечного элемента на подложке кремния: нижний субэлемент на основе гетероперехода A 3 В 5 /Si, где область объемного заряда (ООЗ), в которой происходит наиболее эффективное разделение носителей заряда при поглощении излучения, находится в кремнии с шириной запрещенной зоны E g = 1.12 eV, а верхний субэлемент на основе фотопоглощающих материалов А 3 В 5 с E g = 1.7−1.8 eV. В качестве основы для таких материалов могут использоваться твердые растворы GaP с азотом: тройные соединения GaPN [1], квантово-размерные структуры GaP(N)/InP с большим количеством чередующихся слоев GaP(N) и InP с толщинами от монослоя до 10 nm [2], четверные соединения (In)GaPN(As) [3]. Однако ранее было продемонстрировано повышенное формирование центров безызлучательной рекомбинации в таких полупроводниковых слоях из-за встраивания азота в подрешетку фосфора в GaP, что приводило к низким временам жизни неосновных носителей заряда и низкому КПД фотопреобразовательных структур.…”
unclassified
“…One priority area for photovoltaics is the production of adouble-junction solar cell on a silicon substrate: the lower subcell is based on an A 3 B 5 /Si heterojunction with the space-charge region (SCR), where the process of carrier separation on absorption of radiation is the most efficient, embedded into silicon with bandgap width E g = 1.12 eV, and the upper subcell is based on A 3 B 5 photoactive materials with E g = 1.7−1.8 eV. Solid solutions of GaP with nitrogen (GaPN ternary compounds [1], quantum-dimensional GaP(N)/InP structures featuring a large number of alternating GaP(N) and InP layers with their thickness ranging from a single monolayer to 10 nm [2], and (In)GaPN(As) quaternary compounds [3]) may be used as a base for such materials. However, it has already been demonstrated that non-radiative recombination centers form in greater numbers in semiconductor layers of this kind due to the incorporation of nitrogen into the phosphorus sublattice in GaP, thus shortening the lifetime of minority carriers and reducing the efficiency of photoconversion structures.…”
mentioning
confidence: 99%